Late onset epilepsia partialis continua in a middle-aged patient with huge arachnoid cyst - Mohammad Javad Nasr; Amir Hossein Zohrevand; Ali Alizadeh Khatir (Babol University of Medical Sciences, 2021)
Background: Arachnoid cysts are congenital or acquired cerebrospinal fluid (CSF) filled intra arachnoidal lesions, included 1% of all infantile intracranial masses and were discovered incidentally in MRI or CT-scan. The vast majority of these lesions are generally asymptomatic but some patients with arachnoid cyst have headache, dizziness, seizure (or epilepsy), vestibular symptoms and cognitive impairment. Case Presentation: We present a case of a 43-year-old woman who has late onset epilepsia partialis continua and had right spastic cerebral palsy due to huge arachnoid cyst. Surprisingly without any history of seizure, her first seizure presents with sustained seizures (epilepsia partialis continua) and occur in the middle age for the first time. Conclusion: Most arachnoid cysts are asymptomatic and may not produce any symptoms throughout life. In our case, the late onset epilepsia partialis continua in the 5th decade of life with probably a large arachnoid cyst without any history of seizure before that is unusual. Conservative approaches usually made for the management of arachnoid cysts as patients with these cysts usually maintain the vital neurological functions.